From Inflammation to Current and Alternative Therapies Involved in Wound Healing - Mariana Barreto Serra; Wermerson Assunção Barroso; Neemias Neves da Silva; Selma do Nascimento Silva; Antonio Carlos Romão Borges; Iracelle Carvalho Abreu; Marilene Oliveira da Rocha Borges (International Journal of Inflammation)
Wound healing is a complex event that develops in three overlapping phases: inflammatory, proliferative, and remodeling. These phases are distinct in function and histological characteristics. However, they depend on the interaction of cytokines, growth factors, chemokines, and chemical mediators from cells to perform regulatory events. In this article, we will review the pathway in the skin healing cascade, relating the major chemical inflammatory mediators, cellular and molecular, as well as demonstrating the local and systemic factors that interfere in healing and disorders associated with tissue repair deficiency. Finally, we will discuss the current therapeutic interventions in the wounds treatment, and the alternative therapies used as promising results in the development of new products with healing potential.